Impacts of Surface Ozone Pollution on Global Crop Yields: Comparing Different Ozone Exposure Metrics and Incorporating Co-effects of CO2 - Tai, Amos P. K.; Sadiq, Mehliyar; Pang, Jacky Y. S.; Yung, David H. Y.; Feng, Zhaozhong (Frontiers in Sustainable Food Systems, 2021)
Surface ozone (O3) pollution poses significant threats to crop production and food security worldwide, but an assessment of present-day and future crop yield losses due to exposure to O3 still abides with great uncertainties, mostly due: 1) to the large spatiotemporal variability and uncertain future projections of O3 concentration itself; 2) different methodological approaches to quantify O3 exposure and impacts; 3) difficulty in accounting for co-varying factors such as CO2 concentration and climatic conditions. In this paper, we explore these issues using a common framework: a consistent set of simulated present-day O3 fields from one chemical transport model, coupled with a terrestrial ecosystem-crop model to derive various O3 exposure metrics and impacts on relative crop yields worldwide, and examine the potential effects of elevated CO2 on O3-induced crop yield losses. Throughout, we review and explain the differences in formulation and parameterization in the various approaches, including the concentration-based metrics, flux-based metrics, and mechanistic biophysical crop modeling. We find that while the spatial pattern of yield losses for a given crop is generally consistent across metrics, the magnitudes can differ substantially. Pooling the concentration-based and flux-based metrics together, we estimate the present-day globally aggregated yield losses to be: 3.6±1.1% for maize, 2.6±0.8% for rice, 6.7±4.1% for soybean, and 7.2±7.3% for wheat; these estimates are generally consistent with previous studies but on the lower end of the uncertainty range covered. We attribute the large combined uncertainty mostly to the differences among methodological approaches, and secondarily to differences in O3 and meteorological inputs. Based on a biophysical crop model that mechanistically simulates photosynthetic and yield responses of crops to stomatal O3 uptake, we further estimate that increasing CO2 concentration from 390 ppm to 600 ppm reduces the globally aggregated O3-induced yield loss by 21–52% for maize and by 27–38% for soybean, reflecting a CO2-induced reduction in stomatal conductance that in turn alleviates stomatal O3 uptake and thus crop damage. Rising CO2 may therefore render the currently used exposure-yield relationships less applicable in a future atmosphere, and we suggest approaches to address such issues.